Gugurnya Raja Astina dalam Perang Baratayuda - Anom Sukatno (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2019)
Lakon Gugurnya Raja Astina is also called Rubuhan, which belongs to the Baratayuda series. There were no more reliable Astina. On the eighteenth day of Baratayuda, for the reason, King Duryudana in dealing with the Pandava enemy was led by himself without Kurawa soldiers. On the eighteenth day, it was the last day of Baratayuda War. Senopati Kurawa was the only one, Prabu Duryudana, in a battle against Werkudara. In the war of gada, Prabu Duryudana was forced so he fled to plunge into the sea. Duryudana met Batara Baruna. Batara Baruna gave him Gada Kyai Inten. It cannot be used to fight on the land. Gada Kyai Inten will get smaller when it collids Gada Rujak Polo. The war is witnessed by Baladewa and Kresna. Duryudana was beaten with Gada Rujak Polo by Werkudara and finally, Duryudana died on the battlefield. Keywords: the king of Astina, baratayuda, rubuhan